Resepsi Al-Qur’an Di Pondok Pesantren Tahfidzul Qur’an Al-Ma’ruf Juranguluh Kediri - Afifudin, Ridho; Zayad Abd. Rahman; Ahmad Subakir (Tasamuh: Jurnal Studi Islam, 2025)
This study aims to explore the various forms of Qur’anic reception at the Tahfidzul Qur’an Islamic Boarding School in Juranguluh, Kediri, using a qualitative approach informed by Hans Robert Jauss’s reception theory and Ahmad Rafiq’s typology of Qur’anic reception. Three main forms of reception are analyzed: (1) exegetical reception, manifested through thematic tafsir studies and the understanding of Qur’anic interpretive principles; (2) functional reception, reflected in spiritual routines such as Qur’an completion (khataman), riyāḍah arba‘īn, and the recitation of specific surahs as part of the pesantren’s spiritual and communal life; and (3) aesthetic reception, evident in the training of Qur’anic recitation (tilawah) and calligraphy as expressions of reverence for the sacred text’s beauty. The findings reveal that these forms of reception are integrated into the pesantren’s core curriculum, representing a vision of producing students who embody the Qur’an in recitation, meaning, and practice. Qur’anic reception in this context is not merely theoretical but deeply practical, forming a lived experience and value system within the pesantren. This study contributes significantly to the development of Qur’anic studies grounded in local contexts and affirms the pesantren as a vital living Qur’an space in Indonesian Muslim society.